Cool Places. - Kuizinas, Kestutis; Valatkevicius, Jonas (Vilnius : Contemporary Art Centre, 1998)
Raila, Arturas ; Wretman, Fredrik ; Jansas, Evaldas ; Tonts, Annika ; Zabilevska, Anita ; Narkevicius, Deimantas ; Eliasson, Olafur ; E-LAB ; Alksnis, Arvids ; Kimelis, Peteris ; Ratniks, Martins ; Licis, Dzintars ; Bäckström, Miriam ; Dragset, Ingar ; Elmgreen, Michael ; OLO ; Voukola, Marko ; Karjula, Past ; N55 ; Sorvin, Jon ; Luther, Rikke ; Wendt, Cecilia ; Aarbakke, Ingvil ; Liskevicius, Dainius ; Lejman, Dominik ; Ceponyte, Aida ; Saethre, Borre
biografie
Cool Places, Contemporary Art Centre, Vilnius, 02.10 - 01.11.98
Engels & Litouws
kunstcatalogus